2016
DOI: 10.1186/s13005-016-0125-x
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbiota carriage in patients with multibracket appliance in relation to the quality of oral hygiene

Abstract: BackgroundThe present study aimed to investigate the prevalence of oral microbiota (Candida species (spp.), Streptococcus mutans, and Lactobacilli) in patients with multibracket (MB) appliances in relation to the quality of oral hygiene.Saliva and plaque samples were collected from three groups of 25 patients each (good oral hygiene (GOH), poor oral hygiene (POH), and poor oral hygiene with white spot lesions (POH/WSL)). Counts of colony forming units (CFU) of the investigated oral microbiota were compared usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
0
26
0
2
Order By: Relevance
“…Conventional brackets are often used during orthodontic therapy of patients with malocclusion. The complex construction of such brackets greatly inhibits oral hygiene, which predisposes to increased carriage of bacteria and yeasts [1,2]. An increased amount of fungi in the oral cavity can, with predisposing factors, lead to the development of oral mycosis.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional brackets are often used during orthodontic therapy of patients with malocclusion. The complex construction of such brackets greatly inhibits oral hygiene, which predisposes to increased carriage of bacteria and yeasts [1,2]. An increased amount of fungi in the oral cavity can, with predisposing factors, lead to the development of oral mycosis.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the microbiome through the next-generation sequencing of 16S amplicons (i.e., 16S metabarcoding) offers a cost-effective approach to assess the overall composition of an individual’s microbiome [ 7 , 8 ]. Previous studies have assessed the oral microbiome in relation with factors such as biogeography, environment, age, or ethnicity [ 7 , 9 , 10 ], or have focused on the effect of smoking [ 11 , 12 ], diet [ 13 – 16 ], or hygiene habits [ 17 – 19 ]. On the more clinical side, some studies have uncovered alterations of the oral microbiota in prevalent diseases of the oral cavity including periodontal disease [ 20 ] and caries [ 3 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Klaus et al also reported a significant higher prevalence of Candida spp. associated with poor oral hygiene [42], as confirmed by the literature [64].…”
Section: Protozoas Fungi and Other Bacterial Species In Orthodontic mentioning
confidence: 64%
“…In 2016, Klaus et al reported the results of a cross-sectional study on 75 subjects treated with fixed appliances (mean age, 14.4 ± 1.8 years) to measure the prevalence in saliva and plaque of Candida spp, S. mutans, and Lactobacilli, with culture methods [42]. The subjects were divided according to their oral hygiene status into three groups: good oral hygiene (GOH), poor oral hygiene (POH), and poor oral hygiene with white spots lesions (POH/WL).…”
Section: Fixed Appliances and Cariogenic Speciesmentioning
confidence: 99%